Scripture and Ethics: Twentieth-Century Portraits - Siker, Jeffrey S. (Oxford University Press, Incorporated, 1996)
How should the Bible be used in Christian ethics? Although this question has been addressed many times, little attention has gone to how the Bible actually has functioned in constructing theological ethics. In this book, Siker describes and analyzes the Bible's various uses in the theology andethics of eight of the twentieth century's most important and influential Christian theologians: Reinhold Niebuhr, H. Richard Niebuhr, Bernhard Haring, Paul Ramsey, Stanley Hauerwas, Gustavo Gutierrez, James Cone, and Rosemary Radford Ruether. Of each author Siker asks five related questions: whichbiblical texts does the author in fact use; in what ways are the texts used; how does the author envision the authority of the Bible; what kind of hermeneutic does the author employ; and what has each author's approach to the Bible yielded in terms of Christian ethics? Siker ends each chapter with acritical evaluation of the various problems and prospects for the author's use of Scripture, and concludes the study with a comparison and contrast of the authors' respective appropriations of the Sermon on the Mount.